The future of tourism: interview with Professor Heike Schänzel about her role as Associate Editor of the Journal of Tourism Futures - Ian Seymour Yeoman; Heike A. Schänzel (Journal of Tourism Futures)
Purpose – As the Journal of Tourism Futures celebrates its 10th anniversary, Dr Ian Yeoman (Hotel Management School Leeuwarden) interviews Professor Heike Schänzel (Auckland University of Technology) about her role as the Associate Editor of the journal. Design/methodology/approach – Personal interview. Findings – Schänzel provides a guide to the role of the Associate Editors and discusses her own research. Originality/value – The interview provides insights about the role of Associate Editors in managing the future of tourism and the critical directions of family tourism, lesbian, children’s voices and social justice research.